Psychological And Linguistic Factors In The Process Of Teaching The English Vocabulary - Nasirov, Dilshod (PERFECT EDUCATION FAIRY, 2023)
This article describes the psychological and linguistic factors that determine the process of learning vocabulary. There is also information about the use of words in various situations, performing various exercises using memory, correct pronunciation of words and learning words.